REINFORCING VOCABULARY USING JAZZ CHANT TECHNIQUE - Kalam, Rahmad Hidayatul; ., Sudarsono; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The research investigated the evidence that this technique was useful to use in reinforcing students vocabulary. This was a pre experimental research with one group pre-test and post-test design. There were 10 students which participated in this research. The data were collected by objective tests and analyzed by paired t-test and effect size formula using Cohen’s index. Based on the research findings, the null hypothesis (H0) was rejected, while alternative hypothesis (Ha) was accepted. The t absolute (2.41) was bigger than t critical (1.860) by degree of freedom 8. The effect size was categorized as large effect since the r value was 0.99, bigger than 0.80. To conclude, the use of Jazz Chant technique is significant and very effective to reinforce vocabulary mastery of Year-7 students of SMP Islam Bawari in Academic Year 2015/2016.   Keywords: Reinforce, Jazz Chant technique, Students’ Vocabulary Mastery Abstrak: Penelitian ini menemukan bukti bahwa tehnik Jazz Chant berguna untuk mengasah kemampuan kosakata siswa. Penelitian ini berbentuk eksperimen dengan satu grup pre-test dan post-test. Terdapat 10 siswa yang berpartisipasi dalam penelitian ini. Data diperoleh melalui tes objektif dan dianalisis dengan menggunakan rumus indeks Cohen yaitu uji-t berpasangan dan ukuran efek. Berdasarkan temuan penelitian, hipotesis nol (H0) ditolak, sedangkan hipotesis alternatif (Ha) diterima. t hitung (2.41) lebih besar dari pada t tabel (1.860) dengan derajat kebebasan 8. Ukuran efek dikategorikan sebagai efek besar karena nilai r nya adalah 0.99, lebih besar dibandingkan 0.80. Dapat ditarik kesimpulan bahwa penggunaan Jazz Chant technique adalah penting dan sangat efektif untuk mengasah kemampuan kosakata siswa kelas 7 di SMP Islam Bawari pada tahun akademik 2015/2016.   Kata Kunci: Mengasah, Tehnik Jazz Chant, Kemampuan Kosa Kata Siswa